2007
DOI: 10.1159/000098955
|View full text |Cite
|
Sign up to set email alerts
|

The Antinatriuretic Effect of Insulin: An Unappreciated Mechanism for Hypertension Associated with Insulin Resistance?

Abstract: Insulin resistance is proposed to be causally related to the metabolic syndrome disorders, but a direct cause-and-effect relationship between insulin resistance and hypertension was not originally obvious. Previous data suggested that insulin promotes sodium retention from the kidney, and thus research efforts focused on this action among several other possible pathways connecting insulin resistance and hyperinsulinemia with hypertension. A review of numerous studies provides evidence that this antinatriuretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 162 publications
(112 reference statements)
0
36
0
3
Order By: Relevance
“…Several mechanisms can explain soy protein and isoflavones action on blood pressure: improvement in systemic arterial compliance (29), a natriuretic effect similar to furosemide (30), and amino acid composition (31). It can be hypothesized, in the current study, that insulin concentration decrease in patients with MS using soy protein enriched with isoflavones (data not shown) could lead to lower salt retention and therefore a reduced blood pressure, an underestimated mechanism for hypertension associated with insulin resistance (32). Human studies have also shown that fish oil can lower blood pressure.…”
Section: Discussionmentioning
confidence: 61%
“…Several mechanisms can explain soy protein and isoflavones action on blood pressure: improvement in systemic arterial compliance (29), a natriuretic effect similar to furosemide (30), and amino acid composition (31). It can be hypothesized, in the current study, that insulin concentration decrease in patients with MS using soy protein enriched with isoflavones (data not shown) could lead to lower salt retention and therefore a reduced blood pressure, an underestimated mechanism for hypertension associated with insulin resistance (32). Human studies have also shown that fish oil can lower blood pressure.…”
Section: Discussionmentioning
confidence: 61%
“…Insulin is known to activate the sympathetic nervous system 23 and is a potential mediator of sodium retention and volume expansion and, thus, higher BP. [24][25][26][27] Additional prospective studies of adolescents with larger sample size will, nevertheless, be needed to determine the importance of our observation and to delineate underlying mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity is firmly established as a cause of hypertension, although additional mechanisms besides hyperinsulinemia have been proposed as mechanisms (35,42,56,63). Therefore, it is not surprising that a sodium-retaining action of insulin has continued to be advanced as a contributing factor for sodium retention and hypertension in obesity or metabolic syndrome (53,77,80).…”
Section: Conclusion 1: Insulin Is a Sodium Retainermentioning
confidence: 99%